Black Caribbean men, sexual health decisions and silences - Serrant, Laura (2004)
Sexual health behaviour and the choices people make are influenced by whole range of factors including social grouping, education, peer pressure and access to services/information. Report on the health of the public in Britain have shown that sexual ill health is unequally distributed across society (Department of Health 2001; Royal College of Nursing 2001). people from socially disadvantaged and marginalised groups experience the highest levels of sexually related illness.